2022
DOI: 10.3390/polym14122355
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Atmospheric Conditions on Mechanical Properties of Polyamide with Different Content of Recycled Material in Selective Laser Sintering

Abstract: The price of material is an important factor when selecting the additive polymer procedure. In selective laser sintering (SLS), the price can be reduced by the recycling of material, i.e., with different shares of original and recycled material, as well as by the orientation of the product during manufacturing. Numerous tests warn that orientation in the direction of z axis should be as low as possible to reduce the total price of the product. The product also has to satisfy the influence of atmospheric condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…They reached more than 42% deformation (the limit value for the extensometer used), which is higher than the 20% to 30% deformation of the specimens at the start of aging. These results are consistent with those of previously published works [26][27] . Moisture affects the onyx parts because of the presence of hydrogen in the atomic chain of the ny-lon molecule and the presence of porosity in the parts, which strongly favors moisture absorption.…”
Section: Influence Of Humiditysupporting
confidence: 94%
See 1 more Smart Citation
“…They reached more than 42% deformation (the limit value for the extensometer used), which is higher than the 20% to 30% deformation of the specimens at the start of aging. These results are consistent with those of previously published works [26][27] . Moisture affects the onyx parts because of the presence of hydrogen in the atomic chain of the ny-lon molecule and the presence of porosity in the parts, which strongly favors moisture absorption.…”
Section: Influence Of Humiditysupporting
confidence: 94%
“…Moisture affects the onyx parts because of the presence of hydrogen in the atomic chain of the ny-lon molecule and the presence of porosity in the parts, which strongly favors moisture absorption. Compared with the work of Pilipovic et al [26] , who used a Selective Laser Sintering (SLS) process and a polyamide 12 material, it was found that the impact of moisture on the mechanical properties was less. They discovered that the mechanical properties do not vary after 14 days of exposure; a variation in mechanical properties was observed only after 28 days of exposure.…”
Section: Influence Of Humiditymentioning
confidence: 81%
“…Because of the development of low-cost polymer additive manufacturing, the industry is developing incredibly fast [15,16]. The common processes of 3D-printing technology are fused deposition modeling (FDM), stereolithography (SLA), and selective laser sintering (SLS) [17,18]. In addition, the technology has taken the lead in manufacturing sustainability by reducing the environmental impact [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%